2018
DOI: 10.1007/s11248-018-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Pseudomonas chlororaphis as a gene source for genetically modified crops

Abstract: Genetically modified crops undergo extensive evaluation to characterize their food, feed and environmental safety prior to commercial introduction, using a well-established, science-based assessment framework. One component of the safety assessment includes an evaluation of each introduced trait, including its source organism, for potential adverse pathogenic, toxic and allergenic effects. Several Pseudomonas species have a history of safe use in agriculture and certain species represent a source of genes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
0
30
0
2
Order By: Relevance
“…Importantly, 10 of the 12 selected isolates, i.e., representatives of the genera Acinetobacter, Citrobacter, Pseudomonas, and Serratia, belong to γ-proteobacteria, i.e., a class that comprises a number of human and animal pathogens, including many insect species. Various studies have reported the production of many compounds that inhibit the development of fungi, insects, and nematodes (e.g., phenazine-type antibiotics, hydrogen cyanide, chitinases, and proteases) by P. chlororaphis [48,49]. It has been evidenced that P. chlororaphis injected directly into the hemocoel caused the high mortality of Galleria mellonella (Lepidoptera: Pyralidae) larvae [50].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, 10 of the 12 selected isolates, i.e., representatives of the genera Acinetobacter, Citrobacter, Pseudomonas, and Serratia, belong to γ-proteobacteria, i.e., a class that comprises a number of human and animal pathogens, including many insect species. Various studies have reported the production of many compounds that inhibit the development of fungi, insects, and nematodes (e.g., phenazine-type antibiotics, hydrogen cyanide, chitinases, and proteases) by P. chlororaphis [48,49]. It has been evidenced that P. chlororaphis injected directly into the hemocoel caused the high mortality of Galleria mellonella (Lepidoptera: Pyralidae) larvae [50].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of these similar requirements, in essentially all phyla of host-associated microbiomes, closely related species with pathogenic and beneficial lifestyles can be found (Figure 1). Frequently, relatives with opposite effects are found within the same genus, e.g., among the Paenibacilleae: P. azotofixans and P. amylolyticus (Grady et al, 2016), among Bacilleae: B. velezensis and B. cereus (Radhakrishnan et al, 2017), among Pseudomonas: P. simiae and P. syringae (Anderson et al, 2018) and even within the same species, e.g., Pseudomonas aeruginosa (Steindler et al, 2009;Ndeddy Aka and Babalola, 2016 Phylogenetic tree of plant growth-promoting (black) and pathogenic bacteria (red), and their corresponding phyla (in different shades of gray) mentioned in the text. The tree is supplemented with sequences from some widely applied PGPRs and closely related plant and human pathogens for comparison.…”
Section: Friends or Foes: Closely Related Beneficials And Pathogensmentioning
confidence: 99%
“…This has been successful in maize, in which the expression of an insecticidal protein reduces insect pest damage [61]. Another example is the expression of a gene from the P. chlororaphis isolate G65 to control ethylene production in transformed plants, as summarized in the discussion by Anderson et al [98]. Carlson et al [99] have covered the extensive testing required to demonstrate that genetic modifications are not likely to adversely affect human health.…”
Section: Use Of P Chlororaphis Isolates In Commercial Agricultural Pmentioning
confidence: 99%
“…Studies performed to EPA standards indicate that P. chlororaphis isolates pose limited risks to humans and the environment [98]. The supporting evidence includes the absence of pathogenicity islands and type III/IV transfer systems in bacterial pathogens and that no genes required for the production of toxins characterized from pseudomonad plant pathogens are found in P. chlororaphis isolates.…”
Section: Use Of P Chlororaphis Isolates In Commercial Agricultural Pmentioning
confidence: 99%
See 1 more Smart Citation